Witnesses / Tengku Ibrahim Tengku Kerema - Tengku Kerema, Tengku Ibrahim (Faculty of Law, 1986)
The universal principle of criminal trial, the court should not proceed expert against the accused person. This has been embodied in Section 264 of Criminal Procedure Code which provides:- "Except as otherwise expressly provides all evidences taken under Chapters XVII, XIX, XX, XXI and XXII shall be taken in the presence of the accused or, when his personal attendance is dispensed with in the presence of his advocate." Therefore it is mandatory that all evidences whether for the prosecution or the defence should be taken in the presence of the accused person or in the absence of the accused person, his counsel. This only applies where the accused person or in the absence of the accused person, his counsel.